A brief introduction to Islam - Partridge, Christopher H. (Christopher Hugh), 1961-; Dowley, Tim (Brief introductions., 2018)
This brief introduction to Islam is designed to help readers understand this important religious tradition. Known and valued for its balanced approach, this text provides broad coverage of Islam through an arresting layout with rich colors. The user-friendly content is enhanced by charts of religious festivals, historic timelines, updated maps, and a useful glossary. It is ideal for courses on Islam and will be a useful, concise reference for all readers eager to learn more.